Defect Chemistry: Defect Chemistry in Discharge Products of Li–O2 Batteries (Small Methods 3/2019). Issue 3 (12th March 2019) - Dai, Wenrui; Cui, Xinhang; Zhou, Yin; Zhao, Yong; Wang, Li; Peng, Luming; Chen, Wei
Abstract : In article number1800358, Luming Peng, Wei Chen, and co‐workers discuss the recent progress in understanding and controlling the defect chemistry of discharge products in Li–O2 batteries, including Li + vacancies, dopants, surface/grain boundaries, and amorphous phases, as well as their effects on improving the Li–O2 battery performance.